INTRODUCTION TO ENGLISH LANGUAGE IN EARLY CHILDHOOD EDUCATION - La Jeti; Henny Henny; Siti Misra Susanti (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2018)
This study aims to describe the learning of English vocabulary recognition which includes: Material concept of the introduction of English language applied and how to master English language skills and how to apply early childhood English recognition strategies 6 to 8. This study uses descriptive methods with a qualitative approach. The subjects of the research is the leader and teachers. The setting of the research in Smart School Baubau. The method of Data collection uses observation, interview, documentation. The results showed: 1) In the application of the English introduction learning concepts namely,alphabets, verbs, adjectives, names of animals, names of human body, name of day, months, names of colors, name of family, o'clock, names of fruits, name of accupation, name of shapepronoun, introduction and this concept is easy to understand and interesting for children